Assessing Optimal Digital Elevation Model Selection for Active River Area Delineation Across Broad Regions - Ma, Shizhou; Beazley, Karen F.; Nussey, Patrick; Greene, Christopher S. (Water resources management, 2021)
The Active River Area (ARA) is a spatial approach for identifying the extent of functional riparian area. Given known limitations in terms of input elevation data quality, ARA studies to date have not achieved effective computer-based ARA components delineation, limiting the efficacy of the ARA framework in terms of informing riparian conservation and management. To determine the optimal input elevation data for future ARA studies, this study tested a novel digital elevation model (DEM) smoothing algorithm and assessed ARA outputs derived from a range of DEMs for accuracy and efficiency. It was found that the tested DEM smoothing algorithm allows the ARA framework to take advantage of high-resolution LiDAR DEM and considerably improves the accuracy of high-resolution LiDAR DEM derived ARA results; smoothed LiDAR DEM in 5-m spatial resolution best balanced ARA accuracy and data processing efficiency and is ultimately recommended for future ARA delineations across large regions. The scientific findings provided by this study further enhance the efficacy of the ARA framework, and ultimately the confidence in modelled ARA outputs for application in riparian conservation and management contexts across broad geographic regions.